(untitled) (Research, Society and Development, 2024)
Acute ST-Segment Elevation Myocardial Infarction (STEMI) is a serious condition related to coronary artery disease, characterized by high morbidity and mortality. In this study, carried out with the aim of a comprehensive approach to STEMI, a methodology was adopted that included a systematic literature review, with the selection of nine relevant scientific articles published between 2018 and 2023. The critical analysis of these studies provided an in-depth understanding of the diagnosis, pathophysiology, epidemiology, morbidity and mortality, complications and management of STEMI. The primary therapeutic intervention, coronary angioplasty, was highlighted as crucial in effective reperfusion for affected patients, while fibrinolysis therapy was presented as an alternative in specific situations. The results and discussion derived from this analysis have contributed significantly to the advancement of clinical and scientific knowledge, providing valuable insights to optimize clinical practices and thus improve clinical outcomes in this acute cardiovascular emergency.